Milk market after abolition of milk quotas - Lidia Iurchevici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
In the past two years in Romania, it was recorded one of the sharpest decreases in the amount of cow's milk collected by processing units and at the same time a sharp decline in the price of milk, compared with the average price in the European Union. The obvious conclusion is that milk production in Romania is facing serious problems. This indicates that the milk processing industry and Romanian farmers were not prepared to face the barrier removal of milk quotas. Cattle breeders organizations indicates that many livestock farms in the country are in danger to close due to bad relationship of farmers with processors and repeated delays in paying subsidies from the state. These organizations also argued that the domestic market is flooded with milk imported by the processors, milk that is cheaper because the subsidies granted in countries of origin are higher and received on time. In this context, this study makes an analysis of the current situation of the sector growth of dairy cattle starting from its structure, milk supply (livestock, domestic production, costs of production, import) demand, price capitalization, and finally, based on the analyzed elements, resulting in a series of proposals and recommendations.
Keywords: Q11; Q13; 330; market; quots; milk; production; cattle